The Role of Gender in Public Speaking in Social Layers: A Thorough Examination (Texas Journal of Philology, Culture and History, 2024)
Speaking in front of an audience has always been an essential part of leadership, communication, and social impact. However, a number of characteristics, including gender, affect how well one can communicate and be viewed across social strata. The impact of gender on public speaking is examined in this article, which also examines how prejudices connected to gender affect audience reaction, trustworthiness, authority, and speech delivery. This article clarifies how gender impacts public speaking across social strata by looking at study findings, linguistic theories, and real-world examples. It also provides methods for overcoming communication hurdles based on gender